How a small family run business adopted Critical Reflection Action Learning using hand drawn images to initiate organisational change. (2nd January 2016) - Shepherd, Gary
Abstract : In this account of practice I would like to share my experiences of facilitating a Critical Reflection Action Learning (CRAL) set with a small family run business, struggling to make change and expand their services due to the problems they encountered in separating their business lives from their family lives. The account I present here is based on a 12-session project I carried out with the organisation using a CRAL methodology as part of my Doctoral studies at the University of Hull Business School (Shepherd 2011). In this particular Action Learning project participants were invited to create hand drawn images which acted as representations of the problems they faced as a business. The images were used by set members in reflective conversations on the problems they were having. Each set member cycled through a process of drawing an image and reflecting upon its meaning using individual, group and critical reflection. The whole process enabled set members to gain new insights into their problems and provided them with the opportunity to devise new, more effective ways of tackling their problems and understanding the power dynamics underpinning them.